Effect of fermented Indigofera sp. and turmeric flour on the digestive visceral organs of native chickens - Suci Ananda; Hidayat, Muhammad Nur; Asgaf, Khaifah; Ervandi, Mohamad (Jurnal Ilmu Peternakan Terapan, 2025)
This study aims to evaluate the effect of providing fermented Indigofera sp. leaf flour and turmeric flour on the visceral organs of the digestive tract in native chickens as Kampung Unggul Balitbangtan (KUB). The method employed was a completely randomized design (CRD) with four treatments (T0, T1, T2, and T3) and seven replicates; each unit consisted of one chicken with the following treatment doses, combination between commercial diet, fermented Indigofera sp. leaf flour, and turmeric flour. The measured variables included the weight of digestive organs and the percentage of the length of small intestine segments. Results indicated that administration fermented Indigofera sp. leaf flour and turmeric flour had a significant effect (P<0.05) on the weight of digestive organs and the length of the ileum in KUB chickens, but did not significantly affect (P>0.05) the length of the duodenum and jejunum. The conclusion is that offering fermented Indigofera sp. and turmeric flour at a level of 10% in the diet can improve the efficiency of the KUB chickens digestive system, characterized by a decrease in digestive organ weight.